Hospital Contributory Schemes (letter)
1942-07-20 1942 1940s 5 pages IP Telephone: SLOane 9661. Please address reply (if any) to THE SECRETARY, quoting letter and number MINISTRY OF LABOUR AND NATIONAL SERVICE, Ebury Bridge House, Ebury Bridge Road, London, S.W.1. 20th July, 1942. Dear J.L. Smyth, I think you will be interested to see the enclosed copy of a memorandum by David Ellis on Hospital Contributory Schemes. This memorandum is the result of further research by Ellis and was prepared at the request of the South Wales Advisory Committee. Yours sincerely, L. Taylor [Stamp] 21 JUL 1942 TRADES UNION CONGRESS J.L. Smyth, Esq., Secretary, Social Insurance Dept., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/842/2/172-173